2008
DOI: 10.1111/j.1540-4609.2008.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effectiveness of Web‐Based Homework in Teaching Undergraduate Business Statistics

Abstract: Web-based homework (WBH) Technology can simplify the creation and grading of assignments as well as provide a feasible platform for assessment testing, but its effect on student learning in business statistics is unknown. This is particularly true of the latest software development of Web-based tutoring agents that dynamically evaluate individual students' skill level and purport to respond with appropriate, targeted teaching to improve learning efficiency. In this article, we compare traditional, textbook-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 30 publications
2
48
0
Order By: Relevance
“…In fact, several previous studies (Cooper et al, 1998;Cooper and Valentine, 2001) have found that students who spend more time on doing homework will perform much better in exams than those who do not. In practice, the standard formatted homework (i.e., multiple choice questions) is broadly used (Palocsay and Stevens, 2008). Such homework templates offer several advantages because it is easy to grade, but such approaches also have serious issues.…”
Section: The New Pedagogical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, several previous studies (Cooper et al, 1998;Cooper and Valentine, 2001) have found that students who spend more time on doing homework will perform much better in exams than those who do not. In practice, the standard formatted homework (i.e., multiple choice questions) is broadly used (Palocsay and Stevens, 2008). Such homework templates offer several advantages because it is easy to grade, but such approaches also have serious issues.…”
Section: The New Pedagogical Frameworkmentioning
confidence: 99%
“…They not only need to know the components in the introduced models, but also need to engage in creating model learning that includes how to recombine and redesign multiple models to find the appropriate solution to practical problems. To achieve the goal of getting the creating modelling capability (other similar terminology for the ability includes 'critical thinking' or 'problem solving'), practicing in homework and getting feedback are essential for an undergraduate student in a statistics class (Palocsay and Stevens, 2008;Prybutok et al, 2009). In fact, several previous studies (Cooper et al, 1998;Cooper and Valentine, 2001) have found that students who spend more time on doing homework will perform much better in exams than those who do not.…”
Section: The New Pedagogical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Dufresne et al (2002) found weak evidence that web-based homework improves performance on a physics course compared to traditional paper-and-pencil based homework. On the other hand, Palocsay and Stevens (2008) find little difference between publisher and lecturer designed WBRs for providing supplementary material to undergraduate students on a business statistics course. Other studies compare performance when technology is used to provide supplementary materials rather than simply as an alternative method of provision.…”
Section: Related Literaturementioning
confidence: 99%